Implementasi Produk Kebijakan Pendaftaran Tanah Aset Pemerintah Daerah Kabupaten Pasaman - Farda, Nessa Fajriyana; Syuryani, Syuryani; Amirullah, Imron; Sari, Ice Wahyuni Permata (Asosiasi Ide Bahasa Kepri, 2024)
The government/regional government land asset registration policy is the mandate of Article 43 of Government Regulation Number 27 of 2014 concerning Management of State/Regional Property which states that